2017
DOI: 10.1016/j.addbeh.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Excessive trading, a gambling disorder in its own right? A case study on a French disordered gamblers cohort

Abstract: Our results tended to support the idea of an addictive-like trading behavior as a subset of gambling disorders. Investing is not a form of gambling, but some people gamble with investments. Several observations and recommendations can be made: (i) conduct researches; (ii) build and validate specific assessment tools; (iii) develop strategies for prevention and treatment; and (iv) conduct more rigorous studies to clarify what we named an addictive-like trading behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 24 publications
2
47
0
1
Order By: Relevance
“…There is mounting evidence that stock market trading can become excessive and addictive similar to other behaviors (e.g., Grall-Bronnec et al., 2015; Marković, Nikolac, Tripković, Haluga-Golubović, & Ćustović, 2012; Turner, 2011). In a sample of 582 active Greek stock traders, gamblers, and a control group, Konstantaras and Piperopoulou (2011) found that 11.2% of stock traders demonstrated problematic/compulsive levels of trading.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is mounting evidence that stock market trading can become excessive and addictive similar to other behaviors (e.g., Grall-Bronnec et al., 2015; Marković, Nikolac, Tripković, Haluga-Golubović, & Ćustović, 2012; Turner, 2011). In a sample of 582 active Greek stock traders, gamblers, and a control group, Konstantaras and Piperopoulou (2011) found that 11.2% of stock traders demonstrated problematic/compulsive levels of trading.…”
Section: Resultsmentioning
confidence: 99%
“…However, an implication of the existing research is that because of its apparent strong empirical relationship and moderate conceptual relationship, financial speculation should arguably be listed as an additional activity when assessing both gambling involvement and problem gambling. Although this is sometimes done in population surveys (Williams et al., 2012), and/or in some problem gambling treatment centers (e.g., Grall-Bronnec et al., 2015), it is not routinely included.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, chasing one's losses was also mentioned as a common characteristic between problematic gamblers and online stock traders. This behavior was also observed by Grall-Bronnec et al (2015) in their series of case interviews with excessive stock traders. Chasing losses is considered as the staple criterion of gambling disorder, in that it is what sets gambling disorder apart from other types of addictive disorders (APA, 2013).…”
Section: Links Between Excessive Trading and Gambling Disordermentioning
confidence: 71%
“…Or could it rather be the thrill of the unpredictability and volatility of the market in a short-term time horizon that motivates these traders? In their study, Grall-Bronnec et al (2015) observed that all the excessive stock traders they interviewed were shortterm traders that constantly monitored the market and their titles. This behavior was considered as part of a need for sensation-seeking.…”
Section: Signs Of Excessive Tradingmentioning
confidence: 99%
See 1 more Smart Citation